INACTIVITY BEHAVIOR AND EXERCISE BARRIERS IN PATIENTS WITH BEHCET'S DISEASE - Yentur, S. Baglan; Sarac, D. C.; Tore, N. G.; Sari, F.; Atas, N.; Ozturk, M. A.; Oskay, D. (Elsevier, 2020)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 03, 2020 -- ELECTR NETWORK